Pedological factors affecting pesticide retention in a series of tropical volcanic ash soils in the French West Indies - Campan, Pauline; Samouelian, Anatja; Richard, Antoine; Négro, Sandrine; Lagacherie, Manon; Voltz, Marc (Geoderma Regional, 2024)
Specific pedoclimatic conditions in tropical environments have a considerable impact on pesticide fate. Tropical volcanic soils result from specific pedogenesis processes linked to successive volcanic projections; they are characterised by acidic conditions, high organic matter content, a specific mineralogical composition and the presence of organo-mineral complexes. The retention of pesticides in these soils is therefore often high but variable depending on the associated molecules and soil properties. Nevertheless, knowledge of pesticide sorption in these soils remains limited, and knowledge of the desorption process is scarce. The objectives of this work were to study the variability of the sorption and desorption coefficient of four pesticides currently used in banana and sugarcane crops on a set of representative tropical soils developed on volcanic ash (Guadeloupe, French West Indies). Adsorption and desorption isotherms were analysed for three ionizable pesticides (2,4-D, mesotrione, glyphosate) and a hydrophobic pesticide (difenoconazole) on ten soil samples from five soil profiles: one silandic andosol, one vitric andosol, two nitisols and one ferralsol. For ionizable pesticides, soil pH appears to be a first-order discriminating factor of the sorption capacity, and the organic carbon content appears to have a lesser impact on 2,4-D. For a strongly hydrophobic pesticides such as difenoconazole, the organic carbon content plays a major role in sorption. Desorption hysteresis has been observed regardless of the soils and the molecules considered, and tropical volcanic soils seem to be conducive to adsorption but show low to moderate release. The silandic andosol, which has the greatest sorption, buffers the dissemination of pesticides towards surface and groundwaters but also increases the risk of long-term contamination in the case of molecules that degrade slowly. Moreover, our results highlight that agronomic practices, such as liming, have a major impact on the sorption coefficient of pesticides and must be considered for when predicting sorption in a tropical volcanic context. •The sorption of four pesticides was explored in five different tropical volcanic soils.•Soil characteristics (OC, pH, mineralogy) explain pesticide sorption variability.•Liming tropical volcanic soil greatly impacts the sorption of ionic pesticides.•Need to account for changes in soil properties in contamination schemes.